2023
DOI: 10.1212/wnl.0000000000201448
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Response in Patients With Early Parkinson Disease

Abstract: Background and objectives:The Levodopa in EArly Parkinson´s disease (LEAP) study enabled us to conduct post-hoc analyses concerning the effects of levodopa in patients with early Parkinson’s disease.Methods:The LEAP-study was a double-blind, placebo-controlled, randomized, delayed-start trial in which patients with early Parkinson’s disease were randomized to receive levodopa/carbidopa 300/75 mg daily for 80 weeks (early-start group) or to placebo for 40 weeks followed by levodopa/carbidopa 300/75 mg daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The first double-blind, placebo-controlled trial of levodopa reported a similar long-term effect of levodopa on bradykinesia, rigidity, and tremor [ 74 ]. A recently published post-hoc analysis of the randomized-controlled LEAP-study [ 75 ] also reported similar effect sizes of levodopa for the three cardinal motor domains bradykinesia, tremor, and rigidity in early PD (see Supplementary Material for further details and studies).…”
Section: Drugs Targeting Pd Tremor: Evidence From Trialsmentioning
confidence: 65%
“…The first double-blind, placebo-controlled trial of levodopa reported a similar long-term effect of levodopa on bradykinesia, rigidity, and tremor [ 74 ]. A recently published post-hoc analysis of the randomized-controlled LEAP-study [ 75 ] also reported similar effect sizes of levodopa for the three cardinal motor domains bradykinesia, tremor, and rigidity in early PD (see Supplementary Material for further details and studies).…”
Section: Drugs Targeting Pd Tremor: Evidence From Trialsmentioning
confidence: 65%
“…Besides in-vitro evidence pointing toward a direct neurotoxic effect of L-DOPA or its metabolites, clinical studies have shown no long-term detrimental effects after initiating L-DOPA treatment in PwPD. [24][25][26] In addition, the results of L-DOPA on cerebral bioenergetics within the individual disease course of PwPD (eg, de-novo compared to early-and late-stage PwPD) can only be addressed by longitudinal studies. Longitudinal neuroimaging studies, however, demonstrated that neuronal loss in the SN is more pronounced in the initial compared to later disease stages following a negative exponential function.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal dynamics of these effects have yet to be discovered. Besides in‐vitro evidence pointing toward a direct neurotoxic effect of L‐DOPA or its metabolites, clinical studies have shown no long‐term detrimental effects after initiating L‐DOPA treatment in PwPD 24–26 . In addition, the results of L‐DOPA on cerebral bioenergetics within the individual disease course of PwPD (eg, de‐novo compared to early‐ and late‐stage PwPD) can only be addressed by longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinesia and rigidity usually present a satisfying and sustained response to l ‐dopa while rest‐tremor may be more difficult to treat in some patient. 6 …”
Section: ‐Dopa Responsive Symptomsmentioning
confidence: 99%